دور معلمي الحلقة الأولى في الكشف عن المفاهيم البديلة للتلامذة وتعديلها. دراسة ميدانية في مدينة اللاذقية - جناد روعة عارف; غصون زينب حسين (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
هدفت هذه الدراسة بدايةً إلى الكشف عن دور معلمي الحلقة الأولى في الكشف عن المفاهيم البديلة للتلامذة وتعديلها، من خلال استخدام طرائق تعليمية معينة مناسبة لذلك, كما هدفت أيضاً إلى تحديد الطريقة الأكثر استخداماً عند معلمي الحلقة الأولى, وتعرف تأثير سنوات الخبرة في التعليم على استخدامهم لطريقة معينة دون غيرها في تعديل المفاهيم البديلة للتلامذة. ووفقاً لذلك تم الاعتماد على المنهج الوصفي، إذ صُممت استبانة خاصة لهذا الغرض تضمنت (38) بنداً موزعة على أربعة محاور. وتم توزيع الاستبانة على عينة عشوائية بلغ عددها (105) معلماً ومعلمةً من حملة الإجازة في التربية اختصاص معلم صف. وقد أظهرت الدراسة فاعلية الدور الذي يلعبه المعلمون في الكشف عن المفاهيم البديلة لتلامذتهم وتعديلها بشكل عام, وقد كانت استراتيجيات التغيير المفاهيم يلبوسنرهي الأكثر استخداماً تليها حل المشكلات ثم دورة التعلم, بينما لم تظهر الدراسة أية فروق بين متوسطات درجات المعلمين وذلك في الكشف عن المفاهيم البديلة وتعديلها تبعاً لمتغير سنوات الخبرة في التعليم. وقد أوصت الدراسة بعقد ورشات عمل للمعلمين لتدريبهم على كيفية التعرف على المفاهيم البديلة التي يحملها تلامذتهم, وضرورة إعداد اختبارات تشخيصية للكشف عن تلك المفاهيم قبل البدء بعملية التعليم وفي أثنائها لما في ذلك من أهمية في تطوير أساليب اكتساب المفاهيم. This study aimed at exploring the teachers’ role of the basic teaching of the first cycle of alternative concepts for pupils and modifying them through the use of appropriate teaching methods. It also aimed at determining the most common method used by the teachers of the basic teaching stage and discovering the impact of teaching experience on using a certain method in modifying, alternative concepts for pupils. According to that, the descriptive approach was used. A special questionnaire consisted of (38) items distributed in four fields, it was designed for that purpose. The sample of the research was randomly chosen and consisted of(105) teachers (classroom teacher). The results show a positive role of the teachers of basic teaching stage in the exploration of alternative concepts for their pupils and adjusting them. Posner’s conceptual change strategies were the most commonly used, followed by problem-solving and learning cycle. Whereas the study doesn’t show any statistical differences among the average of the degrees of teachers in the exploration of alternative concepts and adjusted them according to variable of the years of experience in teaching. The study recommended organizing workshops for teachers to train them identify alternative concepts carried by their pupils, and the need to develop diagnostic tests for the exploration of these concepts before starting the process of education and during it. This is due to the importance of the development of acquiring concepts methods.